Faktor-Faktor Yang Memengaruhi Produksi Lada Di Indonesia - Sarianti, Tintin; Waardhana, Finna Denaneera (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Pepper as the leading commodity of the Indonesian plantation sub-sector, is faced by the low productivity of pepper caused by the development of pepper production nationwide is still not optimal and has decreased. In terms of pepper farming, farmers have not fully considered the importance of using production facilities to the yields. The resulting impact is a decrease in the quantity of pepper production that can harm farmers. The purpose of this study is to identify the business practices of pepper farming in Indonesia and analyze the factors affecting pepper production in Indonesia. The source data used in this study were from the 2014 Plantation Household Survey by BPS. The methods used are descriptive analysis and multiple linear regression analysis using the cobb-douglas production function. The production of pepper business in Indonesia can be described by 0.66 kg/tree production, ownership of 1,113 trees, labor use of 159 HOK, NPK fertilizer of 122 kg, urea fertilizer of 154 kg, organic fertilizer of 82 kg, pesticide of 11.4L, uncertified seeds, and monoculture cropping system. Factors that have a positive and significant effect on pepper production are the number of trees, age of plants, labor, NPK fertilizer, pesticides, and dummy cropping system.